The design and application of a disinfection device for ICU nursing (一种ICU护理用消毒装置的设计与应用) - SHI Long (石龙); LU Tingting (卢婷婷); TANG Wei (唐薇); CHEN Yu (陈雨) (中西医结合护理)
This paper introduces a disinfection device for ICU nursing, which achieves the goal of integrated disinfection and drying of medical devices after use. During disinfection, the disinfectant can uniformly act on the surface of medical devices, drying quickly, and is conducive to use. (本研究介绍一种ICU护理用消毒装置, 能够达到医疗器械使用后消毒、烘干一体化效果, 且消毒时消毒液能够均匀作用于医疗器械表面, 干燥快速, 有利于提高消毒效率。)